Occupational Safety And Health (OSH) Practices And Operational Performance In Malaysian Manufacturing Sector - Saad, Mazni (2009)
The manufacturing sector is the backbone of Malaysia’s economy. However, accident statistics for this sector show levels of hazard in the workplace that may reduce the operating ability and efficiency of a firm and consequently lead to a decrease in performance. Meanwhile, OSH practices are acknowledged as an important factor in terms of reducing interruptions to production and eliminating non-added value to business. Thus, the aims of this study are threefold. Firstly it will identify the composition of OSH practices, secondly it will determine the existing OSH practices in manufacturing firms, and thirdly it will examine the relationship between OSH practices and operational performance. Grounded in the domino and sociotechnical theories, OSH practices arise from the existing literature, the government’s guideline, ■ and the practice review in manufacturing firms. As such they are regarded as critical for optimal performance and for meeting government expectations. A mixed-methods approach was used to construct the composition of OSH practices: management commitment, hazard control, training and education, and continual evaluation. OSH practices are proposed as independent variables and operational performance as the dependent variable. This research was conducted on all the manufacturing firms in Malaysia. Of the 329 questionnaires distributed through the Human Resource managers of each firm, the response rate was 44%. A total of 143 full-time production related leaders from supervisory to top management level voluntarily participated in the survey.